2010
DOI: 10.1002/adfm.201001682
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Control of Nucleation Density in Poly(3‐Hexylthiophene) Thin Films

Abstract: solution processing with interesting optoelectronic properties such as high charge transport mobility. Many of the best performing conjugated polymers, including the poly(alkylthiophene)s, derive their high charge mobility from an ability to crystallize. [ 1 , 2 ] While charge transport along an individual conjugated chain is predicted to be extremely rapid, [ 3 ] over longer distances charge must also pass between chains. [ 4 ] Crystallization aids interchain charge transfer by bringing planarized chains tog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
211
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 127 publications
(219 citation statements)
references
References 26 publications
7
211
1
Order By: Relevance
“…Secondly, the crystallization kinetics for growth after nucleation could also influence the crystalline region size. Crossland et al reported that a higher crystallization vapor pressure was helpful for the increase of crystalline region size and alignment order of nanofibrils due to the smaller supercooling and slow crystallization kinetics [159]. Xiao et al observed the gradually increasing length of P3HT needle-like crystals with longer treatment time in THF atmosphere [73].…”
Section: Promotion Of Coil-to-rod Transition and Ordered Rod-rod Stacmentioning
confidence: 99%
See 4 more Smart Citations
“…Secondly, the crystallization kinetics for growth after nucleation could also influence the crystalline region size. Crossland et al reported that a higher crystallization vapor pressure was helpful for the increase of crystalline region size and alignment order of nanofibrils due to the smaller supercooling and slow crystallization kinetics [159]. Xiao et al observed the gradually increasing length of P3HT needle-like crystals with longer treatment time in THF atmosphere [73].…”
Section: Promotion Of Coil-to-rod Transition and Ordered Rod-rod Stacmentioning
confidence: 99%
“…are fixed in this regime influenced by factors such as solvent quality, vapor pressure and treatment time, etc. Firstly, the quality of solvent or vapor atmosphere is important due to its determining on C ∞ and nucleation [79,159,172]. For a bad solubility of solute arising from larger conjugation lengths, bad solvent or smaller vapor pressure, the value of C ∞ is small leading to a small size and larger density of crystallites or even no nucleates.…”
Section: Promotion Of Coil-to-rod Transition and Ordered Rod-rod Stacmentioning
confidence: 99%
See 3 more Smart Citations